Masterplots II : American fiction series / 1: A-Eig - Magill, Frank N. (Frank Northen), ed. 1907-1997. (Englewood Cliffs, N.J. : Salem Press, 1986)
Includes more than 360 interpretative essays on works of twentieth-century fiction published in the United States and Latin America.
Vols. 5-6 published as supplement which updates and extends the original series' coverage--Cf. v. 5, p. xlix.
Includes bibliographies and indexes.
Keywords: Fiction -- 20th century -- Stories, plots, etc; Fiction -- 20th century -- History and criticism; America -- Literatures -- Stories, plots, etc; America -- Literatures -- History and criticism; America -- Literatures -- Stories, plots, etc; America -- Literatures -- History and criticism